1996
DOI: 10.1128/mcb.16.9.5026
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Tyrosine Phosphorylation Sites in ZAP-70 Mediate Activation and Negative Regulation of Antigen Receptor Function

Abstract: Biochemical and genetic evidence has implicated two families of protein tyrosine kinases (PTKs), the Srcand Syk-PTKs, in T-and B-cell antigen receptor signaling. ZAP-70 is a member of the Syk-PTKs that associates with the T-cell antigen receptor and undergoes tyrosine phosphorylation following receptor activation. Three tyrosine residues, Tyr-292, -492, and -493, have been identified as sites of phosphorylation following T-cell antigen receptor engagement. Utilizing ZAP-70-and Syk-deficient lymphocytes (Syk ؊ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
115
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 46 publications
12
115
1
Order By: Relevance
“…It is likely that activation of an alternate threonine-specific phosphatase could occur during CD3/CD28 costimulation, potentially delaying full activation of MAPKs while accelerating cell cycle entry by enhancing singly phosphorylated Cdc2 via decreased threonine phosphorylation. One outcome of T cell activation is cell cycle entry (39), and, at the G 2 -M boundary, Cdc2 becomes dephosphorylated at both Thr 14 and Tyr 15 , resulting in entry into mitosis (40). Complementary information on phosphoserine/threonine protein networks and time-dependent phosphotyrosine activation may answer these questions, but network level quantification for low abundant phosphoserine/threonine proteins remains a challenging task due to the complexity and dynamic range of the serine/threonine phosphoproteome (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that activation of an alternate threonine-specific phosphatase could occur during CD3/CD28 costimulation, potentially delaying full activation of MAPKs while accelerating cell cycle entry by enhancing singly phosphorylated Cdc2 via decreased threonine phosphorylation. One outcome of T cell activation is cell cycle entry (39), and, at the G 2 -M boundary, Cdc2 becomes dephosphorylated at both Thr 14 and Tyr 15 , resulting in entry into mitosis (40). Complementary information on phosphoserine/threonine protein networks and time-dependent phosphotyrosine activation may answer these questions, but network level quantification for low abundant phosphoserine/threonine proteins remains a challenging task due to the complexity and dynamic range of the serine/threonine phosphoproteome (41).…”
Section: Discussionmentioning
confidence: 99%
“…3, B and C). In combination with phosphorylation of other downstream proteins, it seems that phosphorylation at Tyr 292 in Zap70 corresponded with activation of the TCR pathway in this system, although it has been previously implicated in negative regulation using a mutated construct (15). Hierarchical clustering and selforganizing maps clustered Zap70 Tyr 292 with CD3 ITAMs and PLC-␥ (Fig.…”
Section: Regulation Of Tyrosine Phosphorylation In Cd3 Itams and Upstmentioning
confidence: 99%
“…Subsequent phosphorylation of ZAP-70 triggers downstream signaling events that culminate in transcriptional induction of genes that regulate cell function, proliferation and death. 5,6 Similar proximal events including phosphorylation of ITAMS on the immunoglobulin a/b dimer by Src protein tyrosine kinases, and subsequent activation of Syk protein tyrosine kinases have been implicated in the B cell receptor signaling pathway. Mature B cells, however, generally lack ZAP-70 and use the related protein tyrosine kinase, Syk.…”
mentioning
confidence: 97%
“…Mature B cells, however, generally lack ZAP-70 and use the related protein tyrosine kinase, Syk. 5 Recent investigations suggest that ZAP-70 is expressed in early B-cell development and plays a role in the transition of pro-B to pre-B-cell lymphocytes. 1 Additional studies demonstrated increased tyrosine phosphorylated proteins and association of ZAP-70 with IgM and CD79b after ligation of the Bcell receptor in ZAP-70-positive CLL/SLL.…”
mentioning
confidence: 99%
“…In mammal, full catalytic activity of ZAP-70 requires phosphorylation of Y 493 in the activation loop of the kinase domain (Chan et al 1995), and phosphorylated Y 315 and Y 319 in interdomain B are positive regulators of ZAP-70 activity, with the function of stabilization of the active conformation (Di Bartolo et al 2002Gelkop et al 2005;Williams et al 1999). In addition, phosphorylation of specific tyrosine residues, such as Y 292 in interdomain B and Y 492 in the kinase domain, has been implicated in negative regulation of ZAP-70 function (Kong et al 1996).…”
Section: Introductionmentioning
confidence: 99%